Situation report on Nepal’s agrifood systems: June 2024 - Palikhe, A.; Gupta, S.; Maharjan, N.K.; Adhikari, Madan; Kumar, Avinash; Minot, Nicholas; Koirala, P.; Krupnik, Timothy J. (CSISA, 2024)
In May, overall year-on-year inflation stood at 4.4 percent whereas the inflation in food and beverages was 6.3 percent in May 2024 in Nepal. Remittance in the first ten months of the current fiscal year amounted to NPR 1198.6 billion (USD 9 billion), which is a considerable 17 percent higher than the remittance in previous year during same period (in the US dollar terms). The increase in remittances may boost the disposable income of consumers, enhancing their purchasing power for food consumption, though inflation may dampen these effects to a lesser degree. The government of Nepal (GoN) has allocated NPR 27.9 billion (USD 208.4 million) for fertilizer subsidies in its budget for Fiscal Year (FYI 2024/25 (Nepali FY 2081/82), which account for 48.7 percent of the total budget allocated for the Ministry of Agriculture and Livestock Development (MoALD). According to the MoALD, the annual demand for fertilizers is fulfilled through imports in min-June, while the remainder (i.e. 131,000 MT) is expected to arrive in Nepal by third week of June. These arrangements are meant to reduce the demand deficit to around 13 percent of the annual requirement. 1 During the same period, the fiscal policy from the government has lifted the VAT on imports of potatoes, onions and apples FY 2024/25 (Nepali FY 2081/82). This will potentially reduce the retail prices for the commodities in the near future.